PERAN PERPUSTAKAAN SEBAGAI SUMBER BELAJAR - Ahmad Eskha (Jurnal Imam Bonjol: Kajian Ilmu Informasi dan Perpustakaan, 2018)
Abstract: A library is a work unit of an institution that contains a collection of books to support learning resources that are arranged to be read, studied and used as reference material. An educational institution might not be well organized if the teachers and students are not supported by the learning resources needed to organize teaching and learning activities. Smith et al in his encyclopedia book entitled "EDUCATOR'S ENCYCLOPEDIA" states "School Library is a Center for Learning", which means the library is a source of learning. Learning Resources are the main sources, both in the form of data, people and certain forms that can be used by students in learning, separately or in combination so as to facilitate students to achieve learning goals and achieve certain competencies. The learning resource center is a unit within an institution (specifically schools, universities, and companies) that has a full role in promoting the effectiveness and optimization of the learning process through the implementation of various service functions.Keywords: Role, Library, Learning Resources.Abstrak : Perpustakaan adalah suatu unit kerja dari suatu lembaga yang berisi koleksi buku sebagai penunjang dalam meningkatkan sumber belajar yang diatur untuk dibaca, dipelajari, dan dijadikan bahan rujukan. Suatu lembaga pendidikan tidak mungkin dapat terselenggara dengan baik jika para guru dan para siswa tidak didukung oleh sumber belajar yang diperlukan untuk penyelenggaraan kegiatan belajar mengajar. Smith dkk dalam buku ensiklopedianya yang berjudul “EDUCATOR’S ENCYCLOPEDIA” menyatakan “School Library is a Center for Learning”, yang artinya perpustakaan itu merupakan sumber belajar.  Learning Resources merupakan pokok sumber, baik berupa data, orang dan wujud tertentu yang dapat digunakan oleh peserta didik dalam belajar, secara terpisah maupun terkombinasi sehingga mempermudah peserta didik untuk mencapai tujuan belajar dan mencapai kompetensi tertentu. Pusat sumber belajar adalah suatu unit dalam suatu lembaga (khususnya sekolah, Universitas, dan Perusahaan) yang berperan penuh untuk mendorong efektivitas serta optimalisasi proses pembelajaran melalui penyelenggaraan berbagai fungsi layanan.Kata Kunci : Peran, Perpustakaan, Sumber Belajar